Assessing immediate emotions in the theory of planned behavior can substantially contribute to increases in pro-environmental behavior - Ho, Vanessa C.; Berman, Anne H.; Andrade, Jackie; Kavanagh, David J.; Branche, Stéphane La; May, Jon; Philson, Conner S.; Blumstein, Daniel T. (Frontiers in Climate, 2024)
The Theory of Planned Behavior (TPB) is a highly influential and powerful behavior change model that offers promising guidance on promoting urgently needed, pro-environmental action. Recent pro-environmental research has successfully augmented TPB using anticipated emotions—the emotions an individual consciously predicts they will experience in relation to possible outcomes of their decision. However, immediate emotions—the emotions an individual actually experiences during decision-making—have received far less attention. Given that immediate emotions are relevant to pro-environmental decision-making and can address the theoretical and empirical limitations of TPB, we contend that pro-environmental studies should explicitly examine immediate emotions within the TPB framework. This article aims to stimulate rigorous research that enhances pro-environmental communication and policymaking by providing integrative insights into immediate emotions along with recommendations for evaluating immediate emotions in a pro-environmental TPB context.